Lifelines : The Traffic of Trauma. - Solomon, Harris (Durham : Duke University Press, 2022)
Harris Solomon takes readers into the trauma ward of one of Mumbai's busiest public hospitals, narrating the stories of the patients, providers, families, and frontline workers who experience and treat traumatic injury from traffic.
Cover -- Contents -- Note on Illustrations -- Acknowledgments -- Introduction: The Traffic of Trauma -- 1. Carrying: The Lifelines of Transfer -- 2. Shifting: The Lifelines of Triage -- 3. Visiting: The Lifelines of Home -- 4. Tracing: The Lifelines of Identification -- Seeing: The Lifelines of Surgery -- 5. Breathing: The Lifelines of Ventilation -- 6. Dissecting: The Lifelines of Forensics -- 7. Recovering: The Lifelines of Discharge -- Epilogue: The Traffic of Medicine -- Notes -- References -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books